Expanded Hemodialysis: Promising Prospects - M. O Kolesnyk; N. G. Aleksieieva (Transplantation and artificial organs, 2021)
End stage kidney disease (ESKD) causes accumulation of uremic toxins which cover a wide range of molecules classified according to molecular weight into small molecules (<500 Da), medium-sized molecules (500 Da – 60 kDa) and protein-bound toxins.Hemodialysis (HD) remains the main modality of renal replacement therapy in ESKD. Preferably used low-flow dialyzers provided removal of small soluble substances by diffusion, but not clearance of medium-sized molecules.The situation has changed somewhat with the advent of high-flow membranes (HF) and, later, online hemodiafiltration (ol-HDF) which significantly increased the clearance of small and medium-sized molecules due to a combination of diffusion and convection.There is some evidence confirming the hypothesis of insufficient clearance of uremic toxins with higher molecular weight by conventional HD which is the cause of high rates of comorbidity and mortality in patients with ESKD.Specific complications of HD are associated with the accumulation of medium-sized molecules, including myoglobin, leptin, prolactin, fibroblast growth factor (FGF) 23, free light chains kappa and lambda (FLC). Moreover, molecules bound to the proteins like homocysteine, oxidative stress mediators and inflammatory cytokines accelerate the development of atherosclerosis and, as a result, increase cardiovascular mortality.The introduction of MCO membranes into clinical practice has made it possible to develop a new concept of HD therapy called “expanded hemodialysis” (HDx).Thus, new technological solutions concerning the composition of the MCO dialysis membrane enabled to change the dialysis therapeutic targets and combine the capabilities of diffusion and convective transport processes to affect them. Preliminary results demonstrate positive effect of HDx on the triggers of a range of mechanisms of dialysis-associated comorbidity and mortality which can potentially significantly reduce their frequency and/or rate of progression.